2011
DOI: 10.1371/journal.pone.0017887
|View full text |Cite
|
Sign up to set email alerts
|

High Affinity Antigen Recognition of the Dual Specific Variants of Herceptin Is Entropy-Driven in Spite of Structural Plasticity

Abstract: The antigen-binding site of Herceptin, an anti-human Epidermal Growth Factor Receptor 2 (HER2) antibody, was engineered to add a second specificity toward Vascular Endothelial Growth Factor (VEGF) to create a high affinity two-in-one antibody bH1. Crystal structures of bH1 in complex with either antigen showed that, in comparison to Herceptin, this antibody exhibited greater conformational variability, also called “structural plasticity”. Here, we analyzed the biophysical and thermodynamic properties of the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 55 publications
7
72
0
Order By: Relevance
“…On the other hand, the binding free energy has been calculated according to the molecular mechanics-PoissonBoltzmann surface area (MM-PBSA) method. The "in-silico" binding energy ΔG bind is quite large (−285.0 kcalmol -1 ) in comparison with the reported experimental values between −12.4 and −14.0 kcalmol -1 [50,51]. In this sense, Fuentes et al [30] reported an "in-silico" value of ΔG bind 0−1144.6 kcal mol -1 using molecular mechanics-generalized-Born surface area (MM-GBSA) approximation without entropic terms.…”
Section: Principal Component Analysissupporting
confidence: 64%
“…On the other hand, the binding free energy has been calculated according to the molecular mechanics-PoissonBoltzmann surface area (MM-PBSA) method. The "in-silico" binding energy ΔG bind is quite large (−285.0 kcalmol -1 ) in comparison with the reported experimental values between −12.4 and −14.0 kcalmol -1 [50,51]. In this sense, Fuentes et al [30] reported an "in-silico" value of ΔG bind 0−1144.6 kcal mol -1 using molecular mechanics-generalized-Born surface area (MM-GBSA) approximation without entropic terms.…”
Section: Principal Component Analysissupporting
confidence: 64%
“…1, A and B). To accommodate the binding of two structurally unrelated epitopes with essentially the same binding site, 5A12 utilizes a large degree of structural plasticity similar to that described for a Her2/VEGF DAF (44). CDR-H2 in particular undergoes drastic conformational change in the hVEGF-bound state compared with the hAng2-bound state.…”
Section: Resultsmentioning
confidence: 99%
“…On cells with high HER2 density, bivalent binding of COVA420 is facilitated which promotes high avidity. In contrast, CD3/HER2 (scFv)2 is based on a monovalent high-affinity HER2 scFv derived from trastuzumab (Kd = 0.5 nM) [35], that binds to both cell types with similar affinity and hence is incapable of discriminating between high and low HER2 expressing cells.…”
Section: Discussionmentioning
confidence: 99%